The meanings of the Spanish verb (pose) and its derivations and translation into Arabic - Majid Hamood Kadhum Al-Husainawi (Peerian Journals Publishing, 2025)
The research focuses on the verb "poner" in Spanish, examining its various meanings and uses, as well as its translation into Arabic. The objectives include analyzing the meanings and uses of the verb "poner" and its derivations, exploring the colloquial and idiomatic expressions that use it, and studying the grammatical constructions in which it appears, searching for precise equivalents in Arabic. The importance of this study lies in the deep understanding of one of the most versatile verbs in Spanish, which is essential for both native speakers and Spanish learners and translators. This linguistic and cultural analysis helps unravel the subtleties of language and facilitates effective intercultural communication. Accurate translation is crucial, as it must not only convey the literal meaning but also the cultural and contextual nuances inherent to idiomatic and colloquial expressions in Spanish.
Keywords: PONER; Meanings; Derivations